Aesthetics and anaesthetics in Friedrich Nietzsche's philosophy of art - Pannese, A (2024)
This thesis examines aesthetics through the lens of anaesthesia. Focusing on Friedrich Nietzsche's (1844–1900) theory of art, it argues that the anaesthetic forms a critical component of the framework within which Nietzsche developed his aesthetic ideas, and that the anaesthetic dimension operates within Nietzsche's aesthetic discourse as conceptual metaphor, historical context, and material condition.